2012
DOI: 10.1126/science.1217550
|View full text |Cite
|
Sign up to set email alerts
|

Natural SIV Hosts: Showing AIDS the Door

Abstract: Many species of African nonhuman primates are naturally infected with Simian Immunodeficiency Viruses (SIVs) in the wild and in captivity. In contrast to HIV-infected humans, these natural SIV hosts typically do not develop AIDS despite chronic infection with a highly replicating virus. In this review, we will discuss the most recent advances on the mechanisms of protection from disease progression in natural SIV hosts, with emphasis on how they differ from pathogenic HIV/SIV infections of humans and rhesus ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
260
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(265 citation statements)
references
References 70 publications
4
260
0
1
Order By: Relevance
“…When rhesus macaques are infected with SIV, they develop AIDS-like syndromes that are accompanied by massive inflammation, similar to HIV-infected patients; however, African green monkeys (AGM) infected with SIV remain healthy and do not show this chronic inflammation (Chahroudi et al 2012). SIV-infected AGMs show early and strong increases in IL-10, TGF-b, and Foxp3 expression, which oppose findings in infected macaques that show diminished sensitivity to TGF-b signaling in T cells (Kornfeld et al 2005;Ploquin et al 2006).…”
Section: Viralmentioning
confidence: 99%
“…When rhesus macaques are infected with SIV, they develop AIDS-like syndromes that are accompanied by massive inflammation, similar to HIV-infected patients; however, African green monkeys (AGM) infected with SIV remain healthy and do not show this chronic inflammation (Chahroudi et al 2012). SIV-infected AGMs show early and strong increases in IL-10, TGF-b, and Foxp3 expression, which oppose findings in infected macaques that show diminished sensitivity to TGF-b signaling in T cells (Kornfeld et al 2005;Ploquin et al 2006).…”
Section: Viralmentioning
confidence: 99%
“…1,2 The reasons that SIV-infected SMs are resistant to AIDS remain incompletely understood, and it is hoped that their elucidation will help to define the mechanisms responsible for the development of AIDS in HIV-infected humans. 3 Several studies have shown that 2 consistent features of naturally SIV-infected SMs are the absence of generalized immune activation during the chronic phase of the infection and a pattern of in vivo-infected cells that results in a preferential preservation of central memory CD4 ϩ T cells from SIV infection. 4,5 The low immune activation observed in chronically SIVinfected SMs represents a key phenotypic difference from pathogenic HIV/SIV infection of humans and macaques, in which chronic immune activation is a major marker and predictor of disease progression, both in the natural history and in the setting of antiretroviral treatment.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The mechanisms by which SIV-infected SMs are able to tune down their immune activation remain unclear, but may involve specific virus properties, better ability to activate immune regulatory pathways, decreased sensing of viral antigens, preservation of mucosal immunity with consequent absence of microbial translocation, and differences in the pattern and anatomic location of infected cells. 3 Regardless of the mechanisms involved, the low immune activation observed during the chronic phase of SIV infection in SMs is associated with the absence of up-regulation of type I IFN (IFN-I)-stimulated genes (ISGs), which is a consistent feature of the transcriptional profile of pathogenic HIV/SIV infections. 4,13 At this time, however, it remains unknown whether and to what extent this lack of an IFN-I gene-expression signature in chronically SIV-infected natural hosts represents a cause or a consequence of the low immune activation.…”
Section: Introductionmentioning
confidence: 99%
“…In marked contrast, infection of rhesus macaques results in a rapid progression to AIDS that mimics human HIV infection. Unlike pathogenic models, natural primate hosts preserve a healthy level of systemic CD4 + T cells and do not progress to AIDS despite high viremia [73] (reviewed by [74]). One of the main characteristics of this model is the limited immune activation associated with the presence of SIV [75].…”
Section: The Gastro-intestinal Lymphoid Tissue (Galt)mentioning
confidence: 99%
“…Rhesus macaques and humans show a persistent type I interferon response throughout the chronic phase of infection while natural host resolve it within 4 to 8 weeks. Hence, it has been proposed that natural host of SIV actively downregulate the innate and adaptive immune responses to the virus to avoid progression to AIDS (reviewed by [74]). Rapid resolution of innate response might contribute to the maintenance of the mucosal compartment and barrier integrity preventing uncontrolled immune activation and disease progression.…”
Section: The Gastro-intestinal Lymphoid Tissue (Galt)mentioning
confidence: 99%